2014
DOI: 10.1016/j.biortech.2013.10.027
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated decolorization of azo dye Congo red in a combined bioanode–biocathode bioelectrochemical system with modified electrodes deployment

Abstract: h i g h l i g h t sCR decolorization was accelerated with combined bioanode-biocathode BES. The biocathode played an important role in accelerating CR decolorization. Three electrodes deployments were compared based on startup, DE and EIS analysis. The surrounding mode was the best, followed by vertical and horizontal ones. The possible mechanism for the combined bioanode-biocathode was discussed. a r t i c l e i n f o In this study, BES with bioanode and biocathode was applied to decolorize an azo dye Congo r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…The higher current in the integrated system may be attributed to a more efficient electron transfer or a lower cathode resistance . It would cause the stronger stress to induce a higher electrochemical activity based on the electrons interaction between biofilm and the electrode, and resulted in the higher electrochemical reaction kinetics in the integrated system (Kong et al, 2014a), which was consistent to the decolorization results.…”
Section: The Electrochemical Characterization Of the Integrated Systemsupporting
confidence: 73%
See 2 more Smart Citations
“…The higher current in the integrated system may be attributed to a more efficient electron transfer or a lower cathode resistance . It would cause the stronger stress to induce a higher electrochemical activity based on the electrons interaction between biofilm and the electrode, and resulted in the higher electrochemical reaction kinetics in the integrated system (Kong et al, 2014a), which was consistent to the decolorization results.…”
Section: The Electrochemical Characterization Of the Integrated Systemsupporting
confidence: 73%
“…The working volume for the inner anode chamber was 70 mL, resulting in the working volume for cathode to be 210 mL as the module inserted. Both anode and cathode electrode materials were carbon brush (ID 3 cm  8 cm) displaced to be surrounding deployment as described previously with the electrode ratio of 1:3 (Kong et al, 2014a). When the BES module was inserted without anaerobic sludge, it became a sleeve-type BES reactor (Fig.…”
Section: Integrated System Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported the reductive decolorization of azo dyes by the quick cleavage of azo bonds in either traditional dual-chamber BESs Kong et al, 2014Kong et al, , 2013Liu et al, 2009;Mu et al, 2009;Sun et al, 2011) or BESs with the improved configurations (Cui et al, 2012;Hou et al, 2011;Sun et al, 2013;Wang et al, 2013). These studies suggested a promising potential employment of BES for the enhanced degradation of azo dye-laden wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…In order to treat wastewater in more sustainable way, bioelectrochemical system (BES) was introduced to achieve this goal for its resource recovery from wastewater and low energy consumption (Friman et al, 2013;Kong et al, 2014a;Liang et al, 2013;Wang et al, 2011). It has been demonstrated that BES is of great potential for the dechlorination, including reduction at anode and cathode (Aulenta et al, 2011;Chun et al, 2013;Huang et al, 2012;Kong et al, 2014b;Wen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%